f(X) = 9x^3 + 2x^2 - 5x^3 - 7x + 4 and g(X) = 5x^3 - 7x + 4. what is f(X) - g(X)? Show all of your steps and write your final answer in factored form. Please! brainly answers garenteed !!! 50 pts!!!
The answer is simple. Since g(x) is already in the equation 9x^3+2x^2, we know that if fg(x))-g(x) must equal f(x). If x-x=0, then 5x^3-7x+4-5x^3-7x+4. Yet if we simplify, we have the answer 8. So your final answer will be 9x^3+2x^2+8.
Let's solve for f(x). f(x)=9x^3+2x^2−5x^3−7x+4Divide both sides by x: f(x)/x=4x^3+2x^2−7x+4/x f=4x^3+2x^2−7x+4/x To solve for g(x). g(x)=5x^3−7x+4Step 1: Divide both sides by x.g(x)/x=5x^3−7x+4xg=5x^3−7x+4xAnswer:g=5x^3−7x+4/x